EFFECTS OF SIMVASTATIN ON LIPID PROFILE AND NERVE CONDUCTION VELOCITY IN OBESE SPRAGUE DAWLEY RATS - Jabeen, Asma; Khan, Umar Ali; Lodhi, Ghulam Mustafa (Journal of Ayub Medical College Abbottabad, 2011)
Background: The incidence of obesity is increasing worldwide. The lipid derangements and decrease in nerve conduction velocity are important complications for which a number of treatment options are being considered. In this study, Simvastatin, a hydroxyl methyl glutaryl coenzyme A reductase inhibitor is studied for its effects on these complications of obesity. Methods: The study was a randomised control trial conducted at Islamic International Medical College, Rawalpindi in collaboration with Railway General Hospital, Rawalpindi, and National Institute of Health, Islamabad. Ninety adult male Sprague Dawley rats were divided into three groups with thirty rats in each group. One group of rats was taken as control with normal diet while other two groups were given High Fat Diet (HFD) for the whole study period, i.e., 10 weeks. One of the HFD group was given Simvastatin along with high fat diet for four weeks. Lipid profile was done by enzymatic colorimetric method. Conduction velocity of sciatic nerve was determined with the help of PowerLab® data acquisition system. Results: The two groups with HFD showed more than 25% increase in weight at the end of study as compared to control group. HFD group showed significantly higher lipid profile and decreased sciatic nerve conduction velocity when compared with control. The group that was given Simvastatin showed significant improvement in lipid profile and increased sciatic nerve conduction velocity after 4 weeks when compared with the group that was given HFD without any intervention. Conclusions: Simvastatin is effective for improving the lipid profile and sciatic nerve conduction velocity in HFD induced obesity. Keywords: Obesity, Simvastatin, nerve conduction velocity